L'esprit de l'alpinisme Une sociologie de l'excellence en alpinisme, du xixe siècle au début du xxie siècle - Moraldo, Delphine (Sociétés, Espaces, Temps, 2021)
Why do great mountaineers turn away from Everest? Why do they reject the use of artificial oxygen on certain Himalayan summits? Why do they risk their lives for a new ascent? How come they are mostly men - and, until recently, men from the social elites? Ever the theatre of drama, purveyor of heroes and polemics, high level mountaineering is the object of facination. In the discourse surrounding it, the same images reappear: those of a great and noble practice, which cannot be assimilated to a simple sport, with protagonists devoted body and soul, prepared to sacrifice themselves for a new ascent. But only if it is done in the right spirit. Because at the highest level mountaineering still requires that the summit be reached within the strict ethics of the discipline. It is this spirit of mountaineering, synonymous with excellence, that this book questions, through an original historical and sociological survey, using unpublished material, which takes the reader from the origins of mountaineering, in the great English bourgeoisie of the 19th century, to the beginning of the 21st century. The spirit of mountaineering, both as an ethical principle and an esprit de corps, is embedded in hierarchies and relationships of both class and gender domination, which distinguish the elite from the masses, the climbers from the guides, the men from the women. The book reveals how such conceptions continue to reflect the ideologies of the small male elite that codified it over a century and a half ago, surviving the dissemination of mountaineering beyond geographical and social boundaries. The Spirit of Mountaineering will be of interest both to academics and to a wider readership of mountaineering enthusiasts. However, it is an important contribution more generally to all those who question the way in which the structures of social and gender hierarchies are constructed and maintained through time and space.